2011
DOI: 10.2527/jas.2011-3852
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inducing luteal regression before a modified controlled internal drug-releasing device treatment on control of follicular development1

Abstract: At the initiation of most controlled internal drug-releasing (CIDR) device protocols, GnRH has been used to induce ovulation and reset follicular waves; however, its ability to initiate a new follicular wave is variable and dependent on stage of the estrous cycle. The objectives of the current studies were to determine 1) if inducing luteal regression before the injection of GnRH at time of insertion of a CIDR resulted in increased control of follicular development, and 2) if removing endogenous progesterone b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…In beef cows, presynchronization (PG administered 3 d before initiating a 6-d CO-Synch + CIDR TAI protocol) improved follicle turnover in response to GnRH-1 and subsequent pregnancy success compared with a 5 d CO-Synch + CIDR treatment [11]. In addition, heifers were more likely to display estrus and had better follicle turnover after GnRH-1 when presynchronized with PG [12].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In beef cows, presynchronization (PG administered 3 d before initiating a 6-d CO-Synch + CIDR TAI protocol) improved follicle turnover in response to GnRH-1 and subsequent pregnancy success compared with a 5 d CO-Synch + CIDR treatment [11]. In addition, heifers were more likely to display estrus and had better follicle turnover after GnRH-1 when presynchronized with PG [12].…”
Section: Discussionmentioning
confidence: 93%
“…Likewise, a larger proportion of heifers exhibited a new follicular wave at the start of a TAI protocol when they were injected with PG 3 d before the initiation of the protocol [12]. Lactating dairy cows had better pregnancy outcomes during the summer when they were treated with PG and GnRH (3 d after PG and 7 d before the start of the Ovsynch protocol) than cows whose estrous cycles were presynchronized with two PG injections 14 d apart, with the second PG injection administered 10 d before Ovsynch [13].…”
Section: Introductionmentioning
confidence: 99%
“…When luteal regression was induced 3 d before the GnRH injection and insertion of a GIDR in beef heifers, circulating concentrations of progesterone were decreased and less variable compared with heifers that received an initial injection of GnRH at random stages of the estrous cycle. The decrease in circulating concentrations of progesterone tended to increase LH pulse frequency and decrease the variance in follicle size at GIDR removal (Grant et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Increased concentrations of progesterone have been associated with a decreased GnRH-induced LH surge (Colazo et al, 2008). Among heifers, increased concentrations of progesterone had a negative relationship with area under the GnRH-induced LH curve and ovulatory response (Perry and Perry, 2009), and inducing luteal regression 3 d before an injection of GnRH increased the control of follicular tiuuover and growth (Grant et aL, 2011). 489 Induced ovulation of small follicles at the time of fixed-time AI resulted in decreased pregnancy success (Perry et al, 2005;Sa Filho et al, 2010), but when animals were detected in standing estrus ovulatory follicle size had no impact on pregnancy success (Perry et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…However, several studies have reported negative effects on pregnancy success by vaccinating naïve heifers with a MLV at the approximate time of breeding [7,14,15]. Recently developed estrous synchronization or fixed-time AI protocols in heifers try to control follicular development by inducing ovulation at the start of the synchronization protocol; therefore, insemination should occur on the second ovulation after the start of the protocol [8,16]. A review of the literature did not find a study that evaluated the effect of vaccination on estrus synchronization and/or conception on these newly optimized protocols.…”
Section: Introductionmentioning
confidence: 99%